Getting Lost Through the Relational Mail Art of Art/Re-search (T)here: A Decolonizing Methodology - Cloutier, Geneviève; Rowe, Gladys; Flagel, Nadine; Lorenzi, Lucia; Jansen, Irene; Crocker, Wendy; Clare, Adam (Art/Research International)

(untitled) (University of Alberta, 2024)
Art/Re-search (T)here is a SSHRC-funded project that creates new understandings of art, research and decolonized processes amongst theories of knowledge. The relational mail art of Art/Re-search (T)here unfolds through post theories of the (post)qualitative posthumanist philosophies and decolonized practices. These disruptive co-compositions happen by getting lost through thing-power, and through the decolonial project of re-turning to the dynamic whole. (T)here, co-conspirators collaborate through art to reimagine re-search. The project’s initial research questions change alongside co-conspirators in transit as binary knowledge is (un)learned and disrupted. As the mail art travels to entangled spaces, processes are risky, glitchy, (un)known, and trans-formed. In letting go of research questions, art/re-search creates trans-formations. The authors put a call to action for re-searchers to work together through art in ways that question the structure of academia and how we come to know/be. Through relational (un)learning and risk-taking, some-thing lost is getting (t)here.